2018
DOI: 10.1039/c7sc03789a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific detection of protein secondary structure using 2D IR dihedral indexing: a proposed assembly mechanism of oligomeric hIAPP

Abstract: Human islet amyloid polypeptide (hIAPP) aggregates into fibrils through oligomers that have been postulated to contain α-helices as well as β-sheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 81 publications
10
64
0
Order By: Relevance
“…Helices were centered around residues 10–15, displaying a high helical propensity over 0.65 when the number of simulated peptides was less than eight. This result is consistent with a recent 2D infrared spectroscopy (2D IR) study, where residues L12A13 mainly adopted the helical structure, but residues L16V17 did not in the monomeric state . As the number of peptides increased to ten and more, the average helical probability for above residues decreased to around 0.5.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Helices were centered around residues 10–15, displaying a high helical propensity over 0.65 when the number of simulated peptides was less than eight. This result is consistent with a recent 2D infrared spectroscopy (2D IR) study, where residues L12A13 mainly adopted the helical structure, but residues L16V17 did not in the monomeric state . As the number of peptides increased to ten and more, the average helical probability for above residues decreased to around 0.5.…”
Section: Resultssupporting
confidence: 92%
“…Replica exchange MD simulations combined with IMS‐MS experiments demonstrated the intrinsic propensity of hIAPP monomers to form β‐hairpin conformations, which could take place in the oligomers. Depending on experimental conditions of aggregation such as concentrations and the presence of co‐solvents or membranes, the appearance of helical intermediates may vary but the formation of β‐sheet‐rich oligomers should be the obligatory step toward amyloid aggregation. Hence, our study of hIAPP8‐20 aggregation sheds a new light on the aggregation of full‐length hIAPP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short ThT-positive fibrils were even observable immediately after solubilization of N21n. Previous studies have suggested that the segment 20 -29 mediates initial self-recognition and that early oligomers contain stacks of parallel ␤-sheet within the 23 FGAIL 27 region (24,49,50). However, below a critical concentration, IAPP self-recognition appears to be primarily initiated by the N-terminal region, which than propagates to the central domain (51).…”
Section: Self-assembly-toxicity Relationships Of Iappmentioning
confidence: 97%
“…In contrast, by using a helix-disrupting analog, it has been proposed that helical species are off-pathway and that preventing helical folding increases cytotoxicity (23). Moreover, it has been reported that helical conformations are mainly found in the monomeric state and could seed oligomer formation, although they are not mandatory for amyloid growth (24).…”
mentioning
confidence: 99%